If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17x + -5 = 5 + 12x Reorder the terms: -5 + 17x = 5 + 12x Solving -5 + 17x = 5 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -5 + 17x + -12x = 5 + 12x + -12x Combine like terms: 17x + -12x = 5x -5 + 5x = 5 + 12x + -12x Combine like terms: 12x + -12x = 0 -5 + 5x = 5 + 0 -5 + 5x = 5 Add '5' to each side of the equation. -5 + 5 + 5x = 5 + 5 Combine like terms: -5 + 5 = 0 0 + 5x = 5 + 5 5x = 5 + 5 Combine like terms: 5 + 5 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 49s^2-9= | | 0.8x+0.3=9 | | 7.4p-5.3-9.2p=-2.6 | | 9t=-36 | | 15a^2+26a-21=0 | | -x^2+2x+48=0 | | 3x^2=6x-7 | | 0.25x+0.375=0.875 | | 4m-1=5 | | 3p^2+22p-16=0 | | -1.6(x-18)+1.3(x+3)=x+34 | | -x^2+12x+28=0 | | -1.6(x-18)+0.5(x+3)=x-8 | | 11x+8=4x-27 | | x+3/2*8=x/8 | | 4+3a=4(a+2) | | 5b^2-22b+8=0 | | 4z^2+12z-az-3a= | | 6+4n=2 | | T^2+23t+90=0 | | 2b^2+5b-12=0 | | 4=x+14 | | 12b^2-7b+1=0 | | 4=x+10 | | x-18=3x | | 4(x+2y)= | | n-8(1+n)=-4n-32 | | -3y+12=-2(3y+6) | | 4x+3=c | | 5((-8-3y)-2)-2y=-1 | | n-8(1+n)=-4-32 | | y=6x-x^2-8 |